Integrated dry NO sub x /SO sub 2 emissions control system - United States. Department of Energy. (Public Service Co. of Colorado, Denver, CO (United States), 1992)
The DSI system design is approximately eighty percent completed. About eighty percent of the materials have been purchased for erection and setup of the DSI system. Most of the equipment and supply purchases have been made for the DCS. The Unit 4 outage started March 20, 1992 for the installation of the remaining project equipment. overall field construction activities continued on the flyash, boiler, dry sorbent injection and humidification systems. Noell performed startup and testing activities for the urea injection system. FERCO completed baseline urea injection tests March 6, 1992. Preliminary analyses were reviewed at a project review meeting on March 11, 1992. The HVAC platform and duct work for the DCS was installed. B W mobilized on site. Demolition and construction activities began to support the future installation of the low NO, burners and ports. CSM completed the batch reactor vessel. The sorbent and flyash silos were erected for the DSI system. The humidification building was erected and piping for the fly ash silo started.